Sosialiasi dan edukasi bahaya narkoba pada remaja - Lusiana, Evi; Tamzil, Nia Savitri; Oktarina, Desi; Prasasty, Gita Dwi (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2022)
Socialization education of drug abuse for junior high school students are crucial to creating a drug-free generation since junior high school represents the nation's future and will determine its fate. The utilization of counseling lectures and animated movies is one of these methods. This community service activity aims to promote awareness and understanding of the hazards of drugs among the younger generation, particularly SMP N 9 Palembang junior high school pupils. The outcomes of the activity demonstrated an increase in the knowledge, classification, impact, and prevention of drugs among the youth.